Behaviour after Cardiosurgery - Mladinov, Anton (Array, 2010)
Aim of this study was to estimate behavioral changes after cardiac surgery (CS). A questionnaire was sent by mail to 74 women and 122 men during May 2004 and the answers were collected by phone. For statistical analysis, the c2-test was used. A common unhealthy habits before CS were inappropriate diet (80% of all responders), addictions to alcohol (62%) and nicotine (54%). Significantly fewer patients after CS continue with fatty diet (c2=39.069 ; p<0.001), smoking (c2=90.286 ; p<0.001) and alcohol drinking habits (c2=60.667 ; p<0.001). A significant worsening of sexual life (c2= 91.533 ; p<0.001) and significantly less negative influence of weather changes (c2=20.821 ; p<0.001) was found after CS. Men drink more (c2=16.299 ; p<0.001) and smoke more (c2=19.635 ; p<0.001), have better sexual life (c2=17.317 ; p< 0.001), fewer sleeping disorders (c2=17.334 ; p<0.001) and better oral health (c2=38.632 ; p<0.001) than women. These results can be useful for setting up preventive measures for CVD.